2016
DOI: 10.1080/15376516.2016.1196282
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in biomarkers of exposure (BoE) to harmful or potentially harmful constituents (HPHCs) following partial or complete substitution of cigarettes with electronic cigarettes in adult smokers

Abstract: Changes in fifteen urine, blood and exhaled breath BoEs of HPHCs representing classes of compounds reported by FDA to be significant contributors to smoking-associated disease risks were measured in 105 clinical-confined subjects following randomization and a five-day forced-switch from usual brand conventional combustible cigarettes to: (i) exclusive commercial e-cigarette use; (ii) dual-use of commercial e-cigarettes and the subject’s usual cigarette brand; or (iii) discontinued use of all tobacco or nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 45 publications
(48 reference statements)
13
73
0
1
Order By: Relevance
“…Biomarkers for the same compounds declined rapidly in smokers switching to ECs at rates similar to abstinence from smoking over 5 days 52. Neither compound is normally detectable in EC vapour yet both have been shown above to account collectively for more than three-quarters of the cancer potency of tobacco smoke 53.…”
Section: Discussionmentioning
confidence: 97%
“…Biomarkers for the same compounds declined rapidly in smokers switching to ECs at rates similar to abstinence from smoking over 5 days 52. Neither compound is normally detectable in EC vapour yet both have been shown above to account collectively for more than three-quarters of the cancer potency of tobacco smoke 53.…”
Section: Discussionmentioning
confidence: 97%
“…CO also was substantially reduced. O’Connel et al (219, 220), reported on a five day trial of 105 subjects confined to a clinical facility; they found similar reductions in the urinary biomarkers and CO. Lastly, a one-year clinical trial reported significant reductions in exhaled CO (221). Thus, compared to smoking, there appears to be a significant overall reduction in biomarkers for persons completely switching to e-cigs, but it is not known if these peripheral biomarkers reflect effects in the lung.…”
Section: Introductionmentioning
confidence: 90%
“…Four switching studies showed a decrease FeNO (219, 221, 224, 225) (including a 1-year trial), while another found no difference (226), and another with methodological limitations (i.e., e-cigs and controls were tested on different days) reported an increase (227). …”
Section: Introductionmentioning
confidence: 99%
“…A medium‐term biomarker study has shown that, while complete switching to either NRT or e‐cigarettes overwhelmingly reduces exposure to tobacco‐related toxicants, dual use is not associated with any reduction compared with individuals who only smoke . Shorter term studies have shown reductions in toxicants for dual users that are commensurate with the reduction in cigarettes smoked . However, even if dual users displace some tobacco cigarette smoking without adding to nicotine consumption, which represents something of a best‐case scenario, then this may still be of limited potential benefit .…”
Section: Ends and Smoking Cessationmentioning
confidence: 99%